CONFLICT BETWEEN PRIMARY SCHOOLS - Jiemuratov Koblan Utenazarovich (European Journal of Humanities and Educational Advancements, 2021)
In the article discussed various problems and conflicts in the school. The school collective is a large group of people, which includes not only students and teachers, but also parents, and the director, and head teachers, and other employees and institutions. Therefore, one cannot do without controversial points. The most common types of such collisions are: disagreements in the children’s team; misunderstanding between the teacher and the child; disputes between parents and teachers